Best Answer

T + 5 + 3T = 1

Simplify the terms, T and 3T (think 1 apple plus 3 apples)

4T + 5 = 1

Subtract 5 from both sides.

4T = -4

then divide both sides by 4 to get T by itself.

T = -4/4

T = -1

To check, substitute T = -1 wherever you see T in your original equation.

T + 5 + 3T = 1

(-1) + 5 + 3(-1) = 1

4 - 3 = 1

1 = 1 (check)

Q: Find the value in the equation of T plus 5 plus 3T equal 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Trigonometry

Without an equality sign it's not an equation but it can be simplified to: 7x-5

y=6

sin2θ + cos2θ = 1

Presumably this is a quadratic equation question in the form of 35x2+34x+8 = 0 35x2+34x+8 = 0 (7x+4)(5x+2) = 0 Answer: x = -7/4 or x = -2/5 Usually you can factorise a quadratic equation by trial and improvement but in this case it's quicker to use the quadratic equation formula.

It is 0.

Related questions

There is no equation, just an expression. And, since it is an expression, it cannot be solved so w can equal any value whatsoever.

With difficulty because it's not an equation but an expression.

There is no numerical value for 'x' that can make this a true statement.

2x+5 = 62 and 3x-y = 23.3 x = 28.5 and y = 62.2 Solve the first equation and then substitute the value of x into the second equation to find the value of y.

The value of y in the equation -2x plus 4y -4, is 1 plus x/2.

you need to find the value of X first before you can solve this equation

Using the discriminant of b^2 -4ac = 0 the value of k works out as -2

There is no variable, and the equation is not valid.

Presumably this is a simultaneous equation question in the form of: 3x+6y = 48 -5x+6y = 32 Subtract the bottom equation from the top equation in order to eliminate y. Note that 3x - - 5x is equal to + 8x: 8x = 16 Divide both sides by 8 to find the value of x: x = 2 Substitute the value of x into the original equations to find the value y: Therefore: x = 2 and y = 7

In the equation y x-5 2 plus 16 the standard form of the equation is 13. You find the answer to this by finding the value of X.

If tan 3a is equal to sin cos 45 plus sin 30, then the value of a = 0.4.

The solution to this equation is that h is equal to -4. You can substitute this value for h into the equation to get -4 x -9 - 6 plus 12 x -4 plus 40 equals 22, or 36 - 6 plus - 48 plus 40 equals 22.